Fatty acid composition of some Astragalus species from Turkey - Bagci, Eyup (Springer, 2006)
In this study, the fatty acid contents of some Astragalus L. (Fabaceae) species from Turkey were determined by GC and GC-MS techniques. The seed oils of Astragalus sp. (A. echinops Aucher ex. Boiss., A. subrobustos Boriss., A. jodostachys, Boiss. & Buhse., A. falcatus Lam., A. fraxinifolius DC.) contained linolenic (between 23-41.%), linoleic (23-37%), and oleic acids (8-19%) as the major components. Fatty acid composition of the studied Astragalus taxa showed uniform fatty acid patterns. Palmitic and stearic acids were the major saturated fatty acids in the seed oils. The amounts of unsaturated fatty acids were higher than saturated fatty acids.
Keywords: Astragalus L; Fabaceae; fatty acid; chemotaxonomy